2019
DOI: 10.1659/mrd-journal-d-18-00063.1
|View full text |Cite
|
Sign up to set email alerts
|

Encounters Between Experiences and Measurements: The Role of Local Knowledge in Climate Change Research

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Similar to the communities of Savnob and Roshorv, resource-based communities were shown to anticipate changes in temperature by using a set of ecological or sociocultural indicators, such as changes in the timing of agricultural activities, agricultural yields, livestock, infrastructure, or health (c.f. Ayanlade et al 2017;Kieslinger et al 2019;Klein et al 2014). Considering the frequency of reported impacts for each season in Savnob and Roshorv supports this argumentation (Fig.…”
Section: Community Observationssupporting
confidence: 63%
See 4 more Smart Citations
“…Similar to the communities of Savnob and Roshorv, resource-based communities were shown to anticipate changes in temperature by using a set of ecological or sociocultural indicators, such as changes in the timing of agricultural activities, agricultural yields, livestock, infrastructure, or health (c.f. Ayanlade et al 2017;Kieslinger et al 2019;Klein et al 2014). Considering the frequency of reported impacts for each season in Savnob and Roshorv supports this argumentation (Fig.…”
Section: Community Observationssupporting
confidence: 63%
“…ERA5 only showed a significant warming trend for summer, whereas community members identified autumn and winter as warming. Integrative studies in other regions also reported on different trend observations, which they argued with an existing scale mismatch between both knowledge systems (Fernández-Llamazares et al 2017;Kieslinger et al 2019). Whereas in our study a scale mismatch was prevented by downscaling ERA5 data to village-scale, the limited accuracy of the original ERA5 datasets due to missing insitu measurements still influences the spatial accuracy of downscaled temperature estimates and their significance measures.…”
Section: Cogeneration Of Knowledge Across Knowledge Systemsmentioning
confidence: 46%
See 3 more Smart Citations